Effects of seawater acidification and solar ultraviolet radiation on photosynthetic performances and biochemical compositions of Rhodosorus sp. SCSIO-45730 - Wang, Na; Lv, Jinting; Yang, Fangfang; Li, Tao; Wu, Hualian; Li, Chulin; Pei, Haiwei; Wu, Houbo; Xiang, Wenzhou (Frontiers in Marine Science, 2022)
Ocean acidification (OA) caused by rising atmospheric CO2 concentration and solar ultraviolet radiation (UVR) resulting from ozone depletion may affect marine organisms, but little is known regarding how unicellular Rhodosorus sp. SCSIO-45730, an excellent species resource containing various biological-active compounds, responds to OA and UVR. Therefore, we conducted a factorial coupling experiment to unravel the combined effects of OA and UVR on the growth, photosynthetic performances, biochemical compositions and enzyme activities of Rhodosorus sp. SCSIO-45730, which were exposed to two levels of CO2 (LC, 400 μatm, current CO2 level; HC, 1000 μatm, future CO2 level) and three levels of UVR (photosynthetically active radiation (PAR), PAR plus UVA, PAR plus UVB) treatments in all combinations, respectively. Compared to LC treatment, HC stimulated the relative growth rate (RGR) due to higher optimum and effective quantum yields, photosynthetic efficiency, maximum electron transport rates and photosynthetic pigments contents regardless of UVR. However, the presence of UVA had no significant effect but UVB markedly reduced the RGR. Additionally, higher carbohydrate content and lower protein and lipid contents were observed when Rhodosorus sp. SCSIO-45730 was cultured under HC due to the ample HCO3− applications and active stimulation of metabolic enzymes of carbonic anhydrase and nitrate reductase, thus resulting in higher TC/TN. OA also triggered the production of reactive oxygen species (ROS), and the increase of ROS coincided approximately with superoxide dismutase and catalase activities, as well as phenols contents. However, UVR induced photochemical inhibition and damaged macromolecules, making algal cells need more energy for self-protection. Generally, these results revealed that OA counteracted UVR-related inhibition on Rhodosorus sp. SCSIO-45730, adding our understanding of the red algae responding to future global climate changes.